Sustainable livelihoods for the international female migrant youth in South Africa : the case of female refugees in a selected church in Musina - Khutso, Mamadi; Frank, Rapholo Selelo; Justin, Ramoshaba Dillo (Penerbit Universiti Kebangsaan Malaysia, 2022)
This qualitative research sought to explore sustainable livelihoods for the international female migrant youth in South Africa by using a narrative theory. South Africa has a number of the international female migrant youth coming from countries of the Southern African Development Community (SADC) who migrated to the country for better standards of living and sustainable livelihoods. Studies reveal that during their quest to seek a better life, female migrants face various challenges which impede their successful adaptation in South African communities. There are no studies specifically conducted in Musina to allow female migrant youth to narrate strategies for their sustainable livelihoods given the challenges they face. Thus, nine female refugees in a selected church in Musina were conveniently and purposefully selected as a case study to pursue the aim of the current research. Data was collected through semi-structured face to face interviews and were analysed thematically with the assistance of the Nvivo software. Findings reveal that female migrants find it difficult to secure jobs in South Africa because of their undocumented status. For their sustainable livelihoods, female migrant youth employ different strategies to mitigate hunger and unemployment which include street vending, setting up hair salons and doing menial jobs such as cleaning, washing for South African households. The study has also found that female migrant youth have an entrepreneurial mind as they have established certain strategies to survive under extreme hardships. It can thus be concluded from this study that female migrant youth in South Africa are faced with unpleasant challenges upon their arrival leading them to making tough decisions on how they are going to survive, hence their involvement in the informal sector. Skills based programmes to empower immigrants should be established in order to assist those who cannot find employment.